Oreocharis tsaii, a new species of Gesneriaceae from southern Yunnan, China - Yunhong, Tan; Jianwu, Li; Jiantao, Yin (Phytotaxa, 2015)
Oreocharis tsaii, a new species of Gesneriaceae from southern Yunnan, China, is here described and illustrated. It is morphologically similar to O. hirsuta and O. aurea, but can be easily distinguished from the latter by its smaller cordate to ovate leaves; cymes with 1–5 flowers, corolla tube narrowing gradually from base to throat, constricted at the throat, corolla lobes mostly more than half as long as the tube; filaments sparsely glandular-pubescent and pilose, style sparsely glandular-pubescent.